Efficacy and safety of Tongmai Jiangtang capsule combined with conventional therapy in the treatment of diabetic peripheral neuropathy: a systematic review and meta-analysis - Sun, Lin-xi; Li, Yuan-yuan; Xie, Yan-ming (Frontiers in Neurology, 2023)
Background Recently, more and more Chinese patent drugs have been proved to be effective in the treatment of diabetic peripheral neuropathy (DPN). Tongmai Jiangtang capsule (TJC) is one of the representative ones. The present meta-analysis integrated data from several independent studies to determine the efficacy and safety of TJCs combined with routine hypoglycemic therapy for DPN patients, and to evaluate the quality of evidence. Methods SinoMed, Cochrane Library, PubMed, EMBASE, Web of Science, CNKI, Wanfang, VIP databases and registers were searched for randomized controlled trials (RCTs) involving TJC treatment of DPN up to February 18, 2023. Two researchers independently used the Cochrane risk bias tool and comprehensive reporting criteria for Chinese medicine trials to evaluate the methodological quality and reporting quality of the qualified studies. RevMan5.4 was used for Meta-analysis and evidence evaluation, with scores determined for recommendations, evaluation, development and GRADE. The Cochrane Collaboration ROB tool was used to evaluate the quality of the literature. The results of Meta-analysis were represented by forest plots. Results A total of 8 studies were included involving a total sample size of 656 cases. TJCs combined with conventional treatment (CT) could significantly accelerate myoelectricity graphic nerve conduction velocity, including that median nerve motor conduction velocity was faster than those of CT alone [mean difference (MD) = 5.20, 95% confidence interval (CI): 4.31–6.10, P < 0.00001], peroneal nerve motor conduction velocity was faster than those of CT alone (MD = 2.66, 95% CI: 1.63–3.68; P < 0.00001), median nerve sensory conduction velocity was faster than those of CT alone (MD = 3.06, 95% CI: 2.32–3.81, P < 0.00001), and peroneal nerve sensory conduction velocity was faster than those of CT alone (MD = 4.23, 95% CI: 3.30–5.16, P < 0.00001). The total efficiency of the TJCs + CT group was higher than that of the CT group (RR = 1.41, 95% CI: 1.28–1.56, P < 0.00001). The HbA1c after treatment in the TJCs + CT group was lower than that in the CT group (P < 0.05). No adverse drug reactions (ADRs) were reported in the combined TJCs or CT groups. Conclusions TJCs combined with CT reduced the severity of DPN symptoms and no treatment-associated ADRs were reported. However, these results should be considered with caution because there was marked heterogeneity in the research data. Therefore, more stringent RCTs should be designed to validate the efficacy of TJCs in DPN patients. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=264522, identifier: CRD42021264522.